Effects of different exercise doses on cardiorespiratory fitness in young people: a systematic review and meta-analysis - JI, Shuyu; YANG, Zhuyu; WANG, Xiaolin; DONG, Delong (Edizioni Minerva Medica, 2024)
INTRODUCTION: The aim of this article is to explore the optimal exercise dose for improving cardiorespiratory fitness of young people. EVIDENCE ACQUISITION: Web of Science, PubMed, and CNKI databases were used to identify studies. Literature search, data extraction and bias risk assessment were conducted independently by two authors. A total of 25 articles were included, involving 844 young adults with an average age of 17.4±1.7 years. The minimum effective exercise intervention dose (Cohen’s d>0.5) to induce cardiopulmonary enhancement in young adults was 35-50% exercise intensity, 0-35 min exercise time, 2-3 day/week frequency, and 4-5 week exercise duration. The range of exercise intensity, time, frequency, and cycle that have a large effect on improving cardiopulmonary function is 60-69%, 36-45 min and >56 min, 6-7 sessions/week and >8 sessions/week, ≥4 weeks respectively. EVIDENCE SYNTHESIS: The interaction effect results among the elements of exercise prescription: 1) no matter how the single exercise time changes, when the exercise intensity is controlled in the range of 51-70%, there will be a large enhancement effect; 2) when the weekly exercise time is less than 150 min, 51-70% of the exercise intensity will get great enhancement effect; 3) when the weekly exercise time is longer than 150 min, 35-50% and 51-70% of exercise intensity can produce great enhancement effect. A 35-50% exercise intensity, 36-45 min exercise time, ≥8 sessions/ week exercise frequency and 4-5 week exercise duration had the best enhancement effect on male youth. A 51-70% exercise intensity, 36-45 min exercise time, ≥8 sessions/week exercise frequency and 4-5 week exercise duration had the best enhancement effect on female youth. CONCLUSIONS: In conclusion, there was a dose-effect relationship between exercise intervention and improvement of cardiorespiratory fitness in young people. The optimal exercise dose for improving cardiorespiratory fitness in young people was 60-69% exercise intensity, 36-45 min exercise time, ≥8 sessions/week exercise frequency, and 4-5 weeks exercise cycle, respectively. However, attention must be paid to gender differences. COPYRIGHT © 2024 EDIZIONI MINERVA MEDICA.